Cepharanthine suppresses osteoclast formation by modulating the nuclear factor‐κB and nuclear factor of activated T‐cell signaling pathways. Issue 2 (13th November 2018) - Lin, Xixi; Song, Fangming; Zhou, Lin; Wang, Ziyi; Wei, Chengming; Xu, Jiake; Zhao, Jinmin; Liu, Qian
Abstract: The increased activation of osteoclasts is the major manifestation of several lytic bone diseases, including osteoporosis, rheumatoid arthritis, aseptic loosening of orthopedic implants, Paget disease and malignant bone diseases. One important bone‐protective therapy in these diseases focuses on the inhibition of osteoclast differentiation and resorptive function. Given that the deleterious side‐effects of currently available drugs, it is beneficial to search for effective and safe medications from natural compounds. Cepharanthine (CEP) is a compound extracted from Stephania japonica and has been found to have antioxidant and anti‐inflammatory effects. In this study, we found that CEP inhibited receptor activator of nuclear factor‐κB (NF‐κB) ligand (RANKL)‐induced osteoclast formation and bone‐resorbing activities using osteoclastogenesis and bone resorption assay. By polymerase chain reaction, we also found that CEP inhibited the expression of osteoclast‐differentiation marker genes including Ctsk, Calcr, Atp6v0d2, Mmp9 and Nfatc1 . Mechanistic analyses including Western blot and luciferase reporter assay revealed that CEP inhibited RANKL‐induced activation of NF‐κB and nuclear factor of activated T‐cell, which are essential for the formation of osteoclast. Collectively, these data suggested that CEP can potentially be used as an alternative therapy for preventing or treating osteolytic diseases. Abstract : Cepharanthine (CEP), a compound derived from natural products, was found to inhibit receptor activator of nuclear factor‐κB (NF‐κB) ligand (RANKL)‐induced osteoclast formation, the appearance of osteoclast‐specific marker genes, and bone‐resorbing activity. Mechanistically, CEP inhibited the RANKL‐induced activation of NF‐κB as well as the induction of NFATc1, which are essential for osteoclast formation. CEP might be a useful alternative therapy for preventing or treating osteolytic diseases.